Nitric Oxide Plasma Level as a Barometer of Endothelial Dysfunction in Factory Workers - Miyata, Seiko; Noda, Akiko; Hara, Yuki; Ueyama, Jun; Kitaichi, Kiyoyuki; Kondo, Takaaki; Koike, Yasuo (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective Nitric oxide (NO) plays a key role in the regulation of vascular tone and is known as one of the key markers of endothelial dysfunction. We investigated the relationship between NO and risk factors of lifestyle-related disease in factory workers.Methods Our study included 877 factory workers presenting hypertension, dyslipidemia and type 2 diabetes. Oxidated forms of NO, NO2-/NO3- (NOx) plasma concentrations were measured using a colorimetric method.Results NOx plasma levels in patients with lifestyle-related disease were significantly lower than those in the controls. The brachial-ankle pulse wave velocity (baPWV) measured in those patients was significantly greater than that of the controls. Multiple regression analysis revealed that LDL cholesterol was an independent risk factor for reducing NOx plasma concentrations. Interestingly, individuals with low NOx plasma concentrations were more likely to present type 2 diabetes compared to those with the highest plasma levels of NOx (odds ratio [OR] [95% confidence interval; CI]=3.65 [1.61–8.28], P=0.002, 2.67 [1.15–6.20], P=0.022, and 3.27 [1.43–7.48], P=0.005). Subjects with the lowest levels of plasma NOx were more likely to present dyslipidemia (OR [95% CI]=1.69 [1.13–2.53], P=0.01).Conclusion Endothelial function evaluated with plasma NOx may be indicative of lifestyle-related diseases independently from the vascular function assessed using baPWV.
Keywords: nitric oxide; pulse wave velocity; hypertension; dyslipidemia; type 2 diabetes